The Lost Promise of Progressivism - Eisenach, Eldon J. (Book collections on Project MUSE., 1994)
This is a provocative reconsideration of the intellectual origins of Progressivism as it developed from 1885 to the eve of World War I. Eldon Eisenach argues that the Progressives are far more important for our understanding of American culture than we've been led to believe and that they, in fact, established and shaped our most influential institutions - governmental, cultural, educational, religious, professional, economic, and journalistic - as we know them today. Eisenach contends that, despite its demise as a galvanizing force in national party politics, Progressive thought remains a powerful influence in contemporary America. In particular, he shows how Progressive ideas resonate with current debates over individual rights and civic responsibilities, the relationship between the government and the economy, and America's international reputation.